2019
DOI: 10.1016/j.heliyon.2019.e01561
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of potential source rocks of Maastrichtian Araromi formation in Araromi and Gbekebo wells Dahomey Basin, southwestern Nigeria

Abstract: Drilled core samples of the Araromi Formation in the eastern Dahomey basin penetrated by Araromi and Gbekebo exploratory wells were investigated to establish the source rocks potentials in the onshore area of the basin. The sediments are of Maastrichtian age deposited in the shallow marine environment with varying thicknesses. Rock-Eval data of forty seven (40) shales give Total Organic Carbon (TOC) range of 0.50–4.78 wt%, Hydrogen Index (HI) value range of 1 - 327mgHC/gTOC, T max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Major trends of the faults are in the NNE-SSW, NE-SW, NW-SE and WNW-ESE directions, respectively. The faults and fractures are well displayed on the total horizontal derivative map (Figure 8) of the study area and were responsible for fragmenting the basement into several blocks of different magnetic susceptibilities, giving it a rugose horst-graben architecture (Adekeye et al 2019;Onuoha and Ofoegbu 1988;Oladele and Ayolabi 2014;Oladele et al 2016;Okoro and Onuoha 2019). These structures generally influenced the distribution of sub-basins, petroleum systems elements, trap styles, hydrocarbon migration and other resources in the basin.…”
Section: Structural Style Of the Dahomey Basinmentioning
confidence: 98%
See 2 more Smart Citations
“…Major trends of the faults are in the NNE-SSW, NE-SW, NW-SE and WNW-ESE directions, respectively. The faults and fractures are well displayed on the total horizontal derivative map (Figure 8) of the study area and were responsible for fragmenting the basement into several blocks of different magnetic susceptibilities, giving it a rugose horst-graben architecture (Adekeye et al 2019;Onuoha and Ofoegbu 1988;Oladele and Ayolabi 2014;Oladele et al 2016;Okoro and Onuoha 2019). These structures generally influenced the distribution of sub-basins, petroleum systems elements, trap styles, hydrocarbon migration and other resources in the basin.…”
Section: Structural Style Of the Dahomey Basinmentioning
confidence: 98%
“…The general geology ( Figure 2) and tectonostratigraphic sequences of the Dahomey Basin which span from Cretaceous to Recent, and have been studied extensively by many researchers (e.g., Adekeye et al 2019;Omatsola and Adegoke 1981;Billman 1992;Jan Duchene 1998;Omosanya et al 2012;Kaki et al 2013;d'Almeida et al 2016;Akande et al 2018). This includes the Cretaceous Abeokuta Group, which comprise the Ise, Afowo and Araromi Formations; the Palaeocene Ewekoro Formation; the Late Palaeocene to early Eocene Akinbo Formation; the Eocene Oshosun and Ilaro Formations and the Pleistocene to Recent Benin Formation (Figure 3).…”
Section: Location Of Study and Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) is a blend of inland/coastal/offshore basin in the Gulf of Guinea that extends from southeastern Ghana through Togo and the Republic of Benin to southwestern Nigeria 3 , 4 . It is a marginal pull—apart 12 or marginal sag basin 13 , which evolved during the period of rifting in the Late Jurassic to Early Cretaceous times 7 , 8 , 14 . The tectonism was attended by an extended period of thermally induced basin subsidence from the Middle-Upper Cretaceous to Tertiary times as the South American and African tectonic plates entered a drift phase to accommodate the emerging Atlantic Ocean 15 , 16 .…”
Section: Geological Settingmentioning
confidence: 99%
“…Several authors have carried out detailed studies on the stratigraphy, tectonic settings, petroleum potential, foraminiferal biostratigraphy and depositional environments of the Nigerian sector of the Benin Basin (Adekeye & Akande, 2007;Okosun, 1990;Olabode, 2006;Oluwajana et al, 2021;Omatsola & Adegoke, 1981). Ajayi et al (2006) carried out a geochemical study on the Paleogene shales of the Benin Basin and reported an oxygen poor environment for these shales.…”
Section: Introductionmentioning
confidence: 99%